Safety and efficacy of nivolumab for metastatic renal cell carcinoma: real‐world results from an expanded access programme. (23rd July 2018) - De Giorgi, Ugo; Cartenì, Giacomo; Giannarelli, Diana; Basso, Umberto; Galli, Luca; Cortesi, Enrico; Caserta, Claudia; Pignata, Sandro; Sabbatini, Roberto; Bearz, Alessandra; Buti, Sebastiano; Lo Re, Giovanni; et al.
Abstract : Objective: To report the safety and efficacy results of patients enrolled in the Italian Nivolumab Renal Cell Cancer Expanded Access Programme. Patients and Methods: Patients with metastatic renal cell cancer (mRCC) previously treated with agents targeting the vascular endothelial growth factor pathway were eligible to receive nivolumab 3 mg/kg once every 2 weeks. Patients included in the analysis had received ≥1 dose of nivolumab and were monitored for adverse events (AEs) using Common Terminology Criteria for Adverse Events (CTCAE) v.4.0. Results: A total of 389 patients were enrolled between July 2015 and April 2016, of whom 18% were aged ≥75 years, 6.7% had non‐clear cell RCC, 49.6% had bone and 8.2% brain metastases, and 79% had received ≥2 previous lines of therapy. The most common any‐grade treatment‐related AEs were fatigue (13%) and rash (9%). Twenty‐two patients (5.7%) discontinued treatment because of AEs. There were no treatment‐related deaths. The objective response rate was 23.1%. At a median follow‐up of 12 months, the median progression‐free survival was 4.5 months (95% confidence interval 3.7–6.2) and the 12‐month overall survival rate was 63%. Similar survival rates were reported among patients with non‐clear‐cell histology, elderly patients, those with bone and/or brain metastases, and those who had received prior first‐line sunitinib or pazopanib, or prior everolimus. Conclusion: The safety and efficacy observed were consistent with those reported in the pivotal Checkmate 025 trial. Results in patients with non‐clear‐cell mRCC who were elderly, pretreated with everolimus, and had bone and/or brain metastases encourage the use of nivolumab in these categories of patients.